2014
DOI: 10.1371/journal.pone.0094169
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Control in Bilinguals and Musicians: Event Related Potential (ERP) Evidence for Experience-Specific Effects

Abstract: Bilinguals and musicians exhibit behavioral advantages on tasks with high demands on executive functioning, particularly inhibitory control, but the brain mechanisms supporting these differences are unclear. Of key interest is whether these forms of experience influence cognition through similar or distinct information processing mechanisms. Here, we recorded event-related potentials (ERPs) in three groups – bilinguals, musicians, and controls – who completed a visual go-nogo task that involved the withholding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
93
3
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(117 citation statements)
references
References 59 publications
13
93
3
8
Order By: Relevance
“…Unlike the mean amplitude analyses of the sentence judgment components (N400/P600), peak amplitude and peak latency were measured during the N2 (200-350 ms) and P3 (350-500 ms) time windows, both because of the characteristics of the waveforms (the N2/P3 complex provides measurable peaks) and to be consistent with prior research (Moreno et al, 2014). The frontal-central electrode sites were arranged in a 2 (anterior-posterior) by 3 (medial-lateral) grouping (F1, Fz, F2, FC1, FCz, FC2).…”
Section: Go-nogomentioning
confidence: 67%
See 2 more Smart Citations
“…Unlike the mean amplitude analyses of the sentence judgment components (N400/P600), peak amplitude and peak latency were measured during the N2 (200-350 ms) and P3 (350-500 ms) time windows, both because of the characteristics of the waveforms (the N2/P3 complex provides measurable peaks) and to be consistent with prior research (Moreno et al, 2014). The frontal-central electrode sites were arranged in a 2 (anterior-posterior) by 3 (medial-lateral) grouping (F1, Fz, F2, FC1, FCz, FC2).…”
Section: Go-nogomentioning
confidence: 67%
“…Because children are in the process of developing competence across all domains of knowledge, a more stringent test of experience-induced plasticity must be based on evidence from adults. All of the tasks used in the present study have previously demonstrated advantages in fully bilingual adults compared to monolinguals: verbal fluency (letter condition; Luo, Luk, & Bialystok, 2010), metalinguistic task (grammaticality judgment; Moreno, Bialystok, Wodniecka, & Alain, 2010), and nonverbal control (go-nogo; Moreno, Wodniecka, Tays, Alain, & Bialystok, 2014).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Musical experience might therefore lead to general inhibitory control advantages (Moreno & Farzan, 2015). In fact, adult musicians show faster responses than non-musician controls in conflict conditions of both a pitch-based auditory Stroop task and in a visual "Simon Arrows" task (Bialystok & DePape, 2009), musicians outperform non-musicians on a stop-signal task (Strait, Kraus, Parbery-Clark, & Ashley, 2010; see also Moreno, Wodniecka, Tays, Alain, & Bialystok, 2014), and professional musicians show smaller color/word Stroop interference effects than amateur musicians (Travis, Harung, & Lagrosen, 2011). These findings are not limited to college-aged participants: five-year-old children assigned to a four-week intensive computerized musical training improved more than a visual art training control group on a go/no-go task (and showed corresponding changes in electrophysiological responses; Moreno, Bialystok, Barac, Schellenberg, Cepeda, & Chau, 2011).…”
Section: Introductionmentioning
confidence: 97%
“…Several studies have demonstrated enhanced inhibitory control in musicians compared with nonmusician peers, both in musically trained adults (Moussard, Bermudez, Alain, Tays, & Moreno, 2016;Moreno, Wodniecka, Tays, Alain, & Bialystok, 2014;Zuk, Benjamin, Kenyon, & Gaab, 2014;Bialystok & Depape, 2009;Bugos, Perlstein, McCrae, Brophy, & Bedenbaugh, 2007) and in children participating in early childhood music programs ( Joret, Germeys, & Gidron, 2016). Although these group differences could reflect innate predispositions rather than causal effects of training, they are supported by longitudinal evidence for improved inhibitory control with short-term music training (Moreno et al, 2011).…”
Section: Introductionmentioning
confidence: 99%